Prevalence and Risk Factors of Neck Pain among the Hospital Front and Back Office Workers at the Nairobi Hospital, Kenya - Sore, Kwoma Bilton; Otieno, Wycliffe; Stella, Margaret; Ogwedho, Serafino; Muriithi, David; Munyao, Ann; Muya, Christine K.; Karuguti, Wallace (International Journal of Physiotherapy and Research, 2023)
Objective: To identify the prevalence and risk factor of neck pain among the hospital front and back-office workers at The Nairobi Hospital, Kenya. Material and methods: Descriptive cross-sectional studies was carried out among 133 participants on the prevalence and risk factors of neck pain at a specific point of time defined by the population. All variables were collected within a specified duration. An adapted structured close ended questionnaire was used, covering group-made questions for population parameters and variables, for screening neck status for the enrolled participants. In addition to the adapted questionnaire from the Oswestry Neck Disability Index (ONDI) combined with our variables, participants were requested to fill out an adapted combined self-developed questionnaire consisting of demographics characteristics; age, gender, duration of employment, and pain intensity. Collected data was analyzed using statistical package of social sciences-SPSS version 21, and results tabulated in tables, pie charts and graphs. Results: majority of participant ( n=112,84%) were from the age of group between 41-50 years at 42%, followed by 31-40 years at 37%, 21-30 years at 20% and finally 51 years and above at 1%. Females represented by 66% and males at 34% of the participants. Period of employment was between 1-10 years at 60% followed by 11-20 years with 34%, less than 1 year and 21-30 years each represented by 3%. workers currently with neck pain at the Nairobi hospital were (n=38 ,34%). Pain intensity; Majority of those who had neck pain 25% had mild pain, while only 1% had severe pain. Those with risk factors for sitting durations; sitting at 2-4hrs represented by 47.3%, followed by 5-6hrs at 37.5%, less than 2 hours was 8.9%, 7-8hrs was 3.6% and more than 8hrs was 2.7%. Conclusion: study concludes that prevalence of neck pain among front and back-office workers at The Nairobi Hospital currently accounts for 34% with female being the most affected. This is associated with continuous sitting and poor body mechanics in relation to work station and equipment. Age, gender, period of employment, and sitting posture awareness were also found to be important factors influencing the occurrence of neck pain.
Keywords: Neck pain; prevalence; risk factors; Front and back-office workers